ANALISIS PEMBELAJARAN BERDIFERENSIASI DAN PEMAHAMAN SISWA KELAS 7 MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI SMPN 17 KOTA MALANG: , - Lailatul Rofiah; viki zainulrozikan (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2025)
ABSTRACT This study aims to examine the implementation of differentiated instruction and to describe the level of student understanding in the Social Studies subject for Class 7D at SMP Negeri 17 Kota Malang. This research employed a descriptive qualitative approach with data collected through observation, interviews, and questionnaires administered to teachers and students. The findings indicate that differentiated instruction has been initiated in Class 7D through three stages: planning, implementation, and evaluation. In the planning stage, the teacher conducted initial diagnostic assessments. During implementation, various teaching methods were applied, such as group discussions, educational videos, and observation activities. However, the personalization of content and assignments had not been fully realized. Evaluation was carried out through formative and summative assessments, accompanied by feedback to students. The level of student understanding in Social Studies was found to be fairly good. Students were able to comprehend basic concepts, apply the material to real-life contexts, analyze social phenomena, and demonstrate understanding through learning styles that matched their individual profiles. Nonetheless, the application of differentiated instruction still needs to be strengthened in order to make learning more adaptive and to support optimal learning outcom Keywords: Differentiated Instruction, Student Understanding, Social Studies, SMP Negeri 17 Kota Malang